Validation of User Preferences and Effects of Personalized Gamification on Task Performance - Tondello, Gustavo F.; Nacke, Lennart E. (Frontiers in Computer Science, 2020)
Personalized gamification is the tailoring of gameful design elements to user preferences to improve engagement. However, studies of user preferences have so far relied on self-reported data only and few studies investigated the effects of personalized gameful systems on task performance. This study shows that personalized gamification works in practice as predicted by survey studies and leads to higher task performance. We asked 252 participants in two studies to interact with a customized (experimental) or a generic (control) online gameful application to classify images. In the customized version, they could select the game elements that they wanted to use for their experience. The results showed significant correlations between participants' choice of gameful design elements and their Hexad user type scores, which partly support existing user preference models based on self-reported preferences. On the other hand, user type scores were not correlated with participants’ preferred game elements rated after interacting with the gameful system. These findings demonstrate that the Hexad user types are a viable model to create personalized gameful systems. However, it seems that there are other yet unknown factors that can influence user preferences, which should be considered together with the user type scores. Additionally, participants in the experimental condition classified more images and rated their experience of selecting the game elements they wanted to use higher than in the control, demonstrating that task performance improved with personalization. Nonetheless, other measures of task performance that were not explicitly incentivized by the game elements did not equally improve. This contribution shows that personalized gameful design creates systems that are more successful in helping users achieve their goals than generic systems. However, gameful designers should be aware that they must balance the game elements and how much they incentivize each user behaviour, so that the business goals can be successfully promoted. Finally, we analyzed participants’ qualitative answers about their experience with the generic and the customized gameful applications, extracting useful lessons for the designers of personalized gameful systems.